2023
DOI: 10.1088/1402-4896/acd96d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and complexity analysis of a fractional-order memristor conservative chaotic system

Abstract: Memristors are often utilized in circuit model analysis as one of the fundamental circuit components. In this paper, a five-dimensional conservative memristor chaotic system is built after the introduction of the memristor into a four-dimensional conservative chaotic system. The dynamic changes of the system are examined using phase diagram, bifurcation diagram, and the Lyapunov exponent spectrum. A line equilibrium point, symmetry and multi-stability are characteristics of the system, the phase trajectory can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Researchers have found that chaotic systems with high unpredictability, complexity, and sensitive dependence on parameters and initial conditions [1,2] are of great significance in improving the security of encryption algorithms. Depending on whether the system has energy loss or not, we can categorize chaotic systems into dissipative systems [3] and conservative systems [4]. Compared to dissipative systems, conservative systems are better able to cope with the security risk posed by phase space reconfiguration because of the absence of attractors [5,6], and are more stochastic.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that chaotic systems with high unpredictability, complexity, and sensitive dependence on parameters and initial conditions [1,2] are of great significance in improving the security of encryption algorithms. Depending on whether the system has energy loss or not, we can categorize chaotic systems into dissipative systems [3] and conservative systems [4]. Compared to dissipative systems, conservative systems are better able to cope with the security risk posed by phase space reconfiguration because of the absence of attractors [5,6], and are more stochastic.…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly because it gives very accurate models of systems and processes that have memory and are passed down from generation to generation. Fractional-order calculus, which is the generalization of integer-order calculus, has recently gotten a lot of attention because it has many possible uses in biology, earthquake dynamics, chaotic dynamics, electrical circuits, finance, and other fields [3,4]. Recently, some researchers have suggested incorporating fractional calculus into complex networks (CNs) to generate fractional-order complex networks (FOCNs), and they have also discussed the dynamics of FOCNs, including state estimation, synchronization, stability, Mittag-Leffler stability, asymptotic stability, exponential stability, and more [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this paper, we find a new transient transition behavior. In 2023, Leng et al [28] proposed a four-dimensional memristor conservative chaotic system, which has the initial value offset enhancement behavior, and the complexity of chaotic sequence is improved by introducing memristor. In the same year, Li et al [29] proposed a four-dimensional conservative chaotic system, which has many characteristics such as hidden coexistence attractor, initial value shift boosting and so on.…”
Section: Introductionmentioning
confidence: 99%